Study of the mechanical characteristics of coal-serial sandstone after high temperature treatment under true triaxial loading - Shuai Wang; Lianguo Wang; Bo Ren; Ke Ding; Chongyang Jiang; Jiaxing Guo (Scientific Reports, 2023)
Abstract In this study, a series of true triaxial loading tests were carried out on coal-measure sandstone after high temperature treatment by using a self-developed true triaxial test system combined with acoustic emission (AE) monitoring, and the mass loss, deformation characteristics and loss failure mode of sandstone before and after heat treatment were systematically studied. It is found that the true triaxial mechanical properties of sandstone after high temperature treatment are closely related to temperature, and the peak strength, maximum principal strain, volume strain, minimum fracture angle and elastic modulus, which all showed bimodal changes, and 800 °C is the threshold temperature of the first four parameters. The transition temperature of the elastic modulus is 400 °C. It is found that the test results of true triaxial high temperature sandstone are in good agreement with the existing true triaxial theory and test results. The failure forms of the samples at different temperatures show inverted “Y” or inverted “N” shapes. Shear failure occurs when the temperature is below 400 °C, and shear-tension failure occurs when the temperature is above 600 °C. At the same time, it is found that the AE signal has four periods, namely the quiet period, growth period, explosion period and decline period. The number of AE events corresponds to the deviatoric stress interval well. Experimental study of the mechanical properties of sandstone under the coupling effect of high temperature and true triaxial stress has guiding significance for the parameter selection and safety evaluation of roof sandstone in underground coal gasification.